Multi-physics coupling study on thermal energy storage characteristics in closed/abandoned mine shafts - Guoqing ZHANG; Zhan LIU; Zhaoxiang CHU; Furui XI; Liya YANG; Peng HE (Meitan kexue jishu)
Repurposing closed/abandoned mine spaces for renewable energy development serves as an effective approach to achieving carbon peaking and neutrality goals. To explore the technical feasibility of thermal energy storage in abandoned vertical shafts, this study proposes a cyclic water storage system based on coaxial borehole heat exchangers. A transient fluid-solid coupled heat transfer model was developed to characterize thermal interactions between mine water and geotechnical materials. Numerical simulations of thermal storage characteristics were conducted on the approximately 200 m-deep auxiliary shaft of the Xuzhou Woniushan Coal Mine, with model validation achieved through comparison with three experimental datasets from literature. Subsequently, parametric sensitivity analyses were performed to investigate the thermal insulation performance of mine water under natural cooling conditions and the operational characteristics under the thermal storage mode. The results indicate that during the natural cooling phase following rapid heat storage, the thermal loss of shaft mine water exhibits second-order exponential decay characteristics, with 29.73% of the cumulative 100-day heat loss concentrated within the initial 10-day period; higher geothermal gradients (≥0.03 k/m) suppress natural convection and reduce deep-layer heat loss, enhancing thermal preservation; shaft slenderness ratio exhibits a positive correlation with short-term heat loss, yet facilitates higher average water temperatures after long-term storage, favoring geothermal recovery during heating seasons. After comprehensive consideration, a slenderness ratio of 30−50 is recommended for thermal energy storage in mine shafts. Under thermal storage mode, increasing the injection flow rate can rapidly elevate mine water temperature to the desired level in the short term, but this disrupts thermal stratification, significantly reducing storage efficiency, Conversely, raising the upstream heat source temperature enhances the axial water temperature gradient and storage efficiency while decreasing the ratio of heat loss, thus relatively improving thermal storage performance. Moreover, in solar seasonal thermal storage systems without insulation measures on the shaft, a volume-to-collector area ratio (Rv) of 2.5 to 3.0 m3/m2 is advisable to ensure mine water temperatures meet long-term heating demands.